(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2005)
The express-method of qualitative estimation of proazulenes in plants in the basis of microchemical reaction proazulenes with potassium metylate in a phosphoric acid (85 %) is offered. The results of study the proazulenes localization, and also changes of the contents chamazulene in essential oil of Achillea collina from a collection of Nikita botanical garden are given.